Application of Ground-Penetrating Radar for Living Trees Detection - Chen, Shong-Loong; Liu, Sung-Tien; Lin, Chen-Hua; Liu, Chun-Chieh (IOP conference series. Earth and environmental science, 2021)
In order to evaluate the potential hazards, researchers are working on revealing the inner structural of a living trunk using different diagnostic techniques. Nondestructive techniques (NDTs), such as stress wave method and ultrasonic wave method, have become increasingly convenient and economical in trees detection. To improve forest management and to prevent collapses of trees, it is necessary to investigate the internal part of tree trunks. In order to do it non-invasively, ground-penetrating radar (GPR) appears as a promising inspection device. Each of these NDTs has its pros and cons. Among all, the GPR is capable of multiple measurements with hardly any damage to the body of a tree, perfect for investigations on roots and trunks of living trees. 15 camphor trees are selected and subject to GPR testing for the study. The results of inductive method and GPR wave signals indicate that the GPR image shows “wavy” features when an eccentric void is found inside a tree, meaning that the travel time is the shortest for the return signals when the antenna is closest to the void. However, GPR wave signals appear to be discontinuous and fluctuate when there are irregular cavities. The signal time is defined by using the metal plate to generate strong reflection in the case of on-site monitoring. The internal condition of tree trunk is usually tested based on detecting 2D image of tree trunk by the stress wave method, as to confirm that the application of GPR is feasible to detect the trunk of camphor tree. The method proposed in this paper can realize the accurate localization and imaging distribution of the internal defects of the trees by the radar wave scanning images.